Synthesis and Microwave Absorption Properties of Doped Expanded Polystyrene with Silver Nanoparticles - Mohd Arif, Adam Rafiq; Yabagi, Jibrin Alhaji; Hussin, Mohamad Fahmi; See Khee, Yee; Kimpa, Mohammed Isah; Muhammad, Muhammad Nmaya; Agam, Mohd Arif (Journal of Science and Technology, 2017)
Polystyrene (PS) is found to become a future major environmental issue and aggressive attempt by scientists to recycle PS into useful functional, recycle materials are becoming recent research trend. Polystyrene has been considered as a potential conductive and wave absorber materials. Doping PS with metal nanomaterials are found to enhance PS physical properties, thus enable the fine tuning of its conductive and wave absorbing properties. In this report, expanded polystyrene as source of PS waste materials are dissolved in tetrahydrofuran (THF), later added into deionized (DI) water to form precipitate polystyrene nanoparticles. This procedure enables easy access of dope silver (Ag) nanoparticles into PS in a colloidal form especially for homogeneity consideration. The UV-Vis spectroscopy (Ultra-Violet Visible), Field Emission Scanning Electron Microscopy (FESEM), Fourier Transformation Infrared Spectroscopy (FTIR), and Vector Network Analysis (VNA) are used to investigate the doped PS nanocomposite of its morphology, molecular vibrations, electrical and electromagnetic properties. The results indicate promising effects of the electrical and electromagnetic properties of doped polystyrene metal nanocomposite as potential conductive and wave absorber material. Results show that these properties are highly dependent on the type of doping materials.